Qualitative Methodology - Gottschalk, Simon (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The natural science method of hypothesis generation, data collection/analysis, and theory development is both limiting and, as the sole way of understanding human behavior, wrong (Gusfield 2003). By reducing quality to quantity, Bourgois morality economizes on intelligence: It understands reality more cheaply (Barthes 1972).